1997
DOI: 10.1021/np960594c
|View full text |Cite
|
Sign up to set email alerts
|

Argenteanones C−E and Argenteanols B−E, Cytotoxic Cycloartanes from Aglaia argentea

Abstract: Seven new cycloartanes, argenteanones C-E (4-6) and argenteanols B-E (7-10), have been isolated from Aglaia argentea leaves. All of these compounds possess significant cytotoxic activity against KB cells (IC50 values between 3.7 and 6.2 micrograms/mL). Structure elucidation was performed by 2D NMR spectroscopy, aided by molecular modeling in the case of the side chain of compound 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 12 publications
3
19
0
1
Order By: Relevance
“…by the co-occurrence of open-chained derivatives together with two types of cyclic products with tetrahydrofuran (20,24-epoxy) and tetrahydropyran (20,25-epoxy) rings (Joycharat et al, 2008b). Another type of tetrahydrofuran ring in the side-chain was reported for A. argentea Blume, where an 21,23-epoxy ring was formed in the leaves (Omobuwajo et al, 1996a;Mohamad et al, 1997), seeds (Omobuwajo et al, 1996b), and stem bark (Mohamad et al, 1999a), probably representing the precursor of the terminal furan ring typical for limonoids. A similar trend towards an 21,23-epoxy ring was also reported for the bark of A. crassinervia Kurz ex Hiern with an additional formation of a tetrahydropyran (21,24-epoxy) ring (Su et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…by the co-occurrence of open-chained derivatives together with two types of cyclic products with tetrahydrofuran (20,24-epoxy) and tetrahydropyran (20,25-epoxy) rings (Joycharat et al, 2008b). Another type of tetrahydrofuran ring in the side-chain was reported for A. argentea Blume, where an 21,23-epoxy ring was formed in the leaves (Omobuwajo et al, 1996a;Mohamad et al, 1997), seeds (Omobuwajo et al, 1996b), and stem bark (Mohamad et al, 1999a), probably representing the precursor of the terminal furan ring typical for limonoids. A similar trend towards an 21,23-epoxy ring was also reported for the bark of A. crassinervia Kurz ex Hiern with an additional formation of a tetrahydropyran (21,24-epoxy) ring (Su et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, various derivatives of cycloartanes (Inada et al, 1997(Inada et al, , 2001Mohamad et al, 1997;Weber et al, 2000;Joycharat et al, 2008a), tirucallanes (Benosman et al, 1995;Puripattanavong et al, 2000), apotirucallanes (Mohamad et al, 1999a), glabretals (Mulholland and Monkhe, 1993;Su et al, 2006), baccharanes (Hwang et al, 2004a,b), and lupanes (Joycharat et al, 2008a) were also reported for the genus. Recently we established a new series of stereoisomeric 3,4-secodammaranes in A. silvestris (M. Roemer) Merrill, where the tetrahydrofuran (20,24-epoxy) ring linked to the D ring was characterised by the configuration 20R.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristic NMR data suggested that 5 possesses a cycloartane skeleton, which has been reported as one of the major classes of triterpenes isolated from Aglaia species. 38,[44][45][46][47][48] In the HMBC spectrum, observed correlations from H-2, H 3 -28, and H 3 -29 to C-3, as well as H-22 to C-21 and C-17, and H-21 to C-22 supported the location of hydroxy groups at C-3 and C-22, respectively. The protons of two geminal methyls, H 3 -26 and H 3 -27, showed correlations with the Δ 24 double bond carbons, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…This observation explained the different coupling pattern observed for H-3 (δ H 3.22, 1H, ddd, J = 10.4, 9.0 and 4.5 Hz), when compared with H-3 (δ H 3.28, 1H, dd, J = 10.8 and 4.4 Hz) of 3β-hydroxy cycloartane derivatives. 38,[44][45][46][47][48] The absolute configuration of C-3 was also determined as S by the Mosher ester procedure (Figure 4). A NOESY experiment revealed the consistent relative configuration of 7 with other cycloartane analogues isolated in this investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation